(untitled) (PJDOL, 2023)
This study explores private sector sources of participation in the management of open and distance learning in Nigeria. Fourteen private sector sources were derived for the study, and respondents were required to score each of the sources between ‘1’ and ‘14’ for the promotion of private sector participation in education of open and distance learning. The instrument was administered to 400 facilitators (teachers) in the open and distance learning/study centres.